“School is awful, horrible and like a prison.” A reflexive thematic analysis of primary school pupils’ perceptions of the factors which influence their school attendance - Wright, Sophie (2023)
Difficulties with school attendance have been linked to poorer academic attainment, as well as later unemployment and reduced emotional wellbeing. This is a particularly pertinent area of research following the impact of the Covid-19 pandemic. It is also an area of interest for the UK government, with the Department for Education (DfE, 2022) having recently published guidance on supporting school attendance. Research highlights the benefits of early identification and intervention for these needs, as well as the importance of gaining pupil voice. However, there has been limited research focussing on primary school aged children and young people (CYP)’s views, despite the literature suggesting that barriers to school attendance do begin in primary school.